2021
DOI: 10.3390/molecules26061623
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the Reaction of Alexidine with Sodium Hypochlorite: A Potential Error in Endodontic Treatment

Abstract: Therapeutic success in endodontic treatment depends on successful infection control. Alexidine dihydrochloride (ALX) was recently proposed as a potential alternative to 2% chlorhexidine (CHX) as it possesses similar antimicrobial properties, expresses substantivity and does not produce p-chloroaniline (PCA) when mixed with sodium hypochlorite (NaOCl). However, the products released in this reaction have not been described to date. The aim of this study was to identify detected chemical compounds formed in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…11,19 It was recommended that ALX and NaOCl should be used without mixing during endodontic irrigation since aliphatic amines which are the products of this reaction have neurotoxic properties. 13 Also in our study ALX and NaOCl did not used consecutively.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…11,19 It was recommended that ALX and NaOCl should be used without mixing during endodontic irrigation since aliphatic amines which are the products of this reaction have neurotoxic properties. 13 Also in our study ALX and NaOCl did not used consecutively.…”
Section: Discussionmentioning
confidence: 82%
“…19,20 On the contrary, in a recent study, it was reported that a yellowish precipitate was formed by the interaction of NaOCl and ALX, but PCA was not formed. 13 Unlike PCA 12 , SEM (Scanning Electron Microscope) images in previous studies revealed that this precipitate did not occlude dentin tubules, so does not compromise the quality of the root canal filling in terms of microleakage. 11,19 It was recommended that ALX and NaOCl should be used without mixing during endodontic irrigation since aliphatic amines which are the products of this reaction have neurotoxic properties.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Drug–drug interactions : To enhance the bactericidal effect of sodium hypochlorite, other agents have been advocated in root canal irrigation protocols. Although it was already known that a mixture of sodium hypochlorite with chlorhexidine produces p-chloroaniline as a toxic by-product, as well as brown precipitates, the mixture with alexidine dihydrochloride results in formation of aliphatic amines and should also be avoided ( Czopik et al, 2021 ) [E].…”
Section: Halogensmentioning
confidence: 99%